An achievement test in English for Grade six - Balagot, Lydia (Ramos) 1929- ([Quezon City publisher not identified], 1969)
The study is a seminar paper about an achievement test in English divided into two equivalent forms, which aims to measure the sixth grade pupil's achievement and growth in the three elements of language-pronunciation, vocabulary, and grammatical structure. It also aims to show how a test in English can be constructed so as to measure pupil proficiency in the language.
Thesis (Master of Arts in Teaching(English))--University of the Philippines
Keywords: English language -- Examinations, questions, etc